Pembelajaran Kertas Kokoro untuk Melatih Motorik Halus Anak di PPT Sekar Wangi Kecamatan Pakal Surabaya - Ashar, Salim; Wahyudi, Mukhammad; Nur Arifah, Naima; Junaidi Musthofa, Ahmad (Journal of Early Childhood Education Studies, 2025)
The Fine motor skills are crucial for early childhood development because they are directly related to basic skills such as writing, drawing, assembling, and other daily activities that require coordination and precision of movement. One way to develop this aspect is through fun, creative activity-based learning. This study aims to explore the application of learning activities using kokoru paper to develop children's fine motor skills at the Sekar Wangi Child Development Center (PPT) in Pakal District, Surabaya. The learning method used was hands-on, with children being invited to create sunflower crafts from kokoru paper, following the steps of cutting, rolling, and gluing. This process provided a stimulus that stimulated hand-eye coordination, finger strength, concentration, and the ability to follow instructions. Furthermore, this activity encouraged children's creativity and independent self-expression. The results showed that most children successfully completed the tasks and demonstrated significant progress in fine motor skills. Even children who previously struggled were able to show gradual progress with appropriate guidance. Thus, kokoru paper-based learning has proven to be an effective, enjoyable approach that supports optimal child development in early childhood.